Effect of Pomegranate Juice Consumption on Plasma Indole Propionic Acid, a Bacterial-Derived Tryptophan Metabolite (P20-003-19). (13th June 2019) - Henning, Susanne; Yang, Jieping; Lee, Rupo; Huang, Jianjun; Small, Gary; Guo, Yuanqian; Heber, David; Li, Zhaoping
Abstract: Objectives: The gut microbiota produces numerous metabolites from dietary nutrients that can circulate systemically and influence the host physiology. Bacterial enzymes convert dietary L-tryptophan (Trp) to indole, from which several metabolites can be formed by mammalian and bacterial enzymes. The bacterial metabolite indole propionic acid (IPA) is anti-inflammatory, neuroprotective and has been linked to a lower risk of type 2 diabetes. Little is known about which bacteria are responsible for IPA formation. Pomegranates (Pom) are excellent sources of ellagitannins (ET) and ellagic acid (EA) with prebiotic function. Therefore, it was our hypothesis that long-term Pom consumption will change bacterial Trp metabolite formation. Methods: We performed a 12-month, randomized, double-blind, placebo-controlled trial of pomegranate juice in middle-aged and older, healthy adults. Nineteen subjects (ages 50–60) were randomized to consume 8 oz of pomegranate juice (the Wonderful Company, LLC) ( N  = 11) or placebo drink ( N  = 8) every day. The placebo drink contained high fructose corn syrup, Pom essence and flavor and FD&C Red#40, Blue#1. Stool samples were collected at baseline and after 1 year of Pom J consumption. Bacterial composition was determined using 16S rRNA microbiome sequencing. Plasma IPA concentrations were determined by HPLC. Correlation between fecal bacterial content and plasma IPA was evaluated in all samples using Spearman's analysis. Results: The IPA was significantly reduced in the placebo group ( P  = 0.017), while there was no change in the Pom J group ( P  = 0.458). The change in plasma IPA during one year of Pom J compared to placebo drink consumption was significantly different ( P  = 0.028). At 12 months, plasma IPA concentration was significantly positively correlated with the relative proportion of Roseburia (0.57), Lachnospira (0.53) in the phylum Firmicutes; Sutterella (0.63) in the phylum Proteobacterium and Collinsella (0.46) in the phylum Actinobacteria. A significant negative correlation was observed with the relative proportion of Campylobacteraceae (−0.46). Conclusions: Formation of IPA associated with a microbial profile supported by Pom J consumption might contribute to the cardiovascular health benefits of Pom. Funding Sources: Supported by Center for Human Nutrition, UCLA.